Ventilation through a single port. (November 2022) - Bejan, A.; Almahmoud, H.; Gunes, U.
Abstract: This is a fundamental study of the periodic in & out flow through a single orifice into an enclosure. The purpose of the 'breathing' flow is to refresh the enclosure air. The injected air differs from the original enclosure air with respect to concentration of undesirable components or temperature. Two scenarios are considered. (i) Single puff of fresh air injected during an interval t1, followed by a pause t0, and extraction of mixed enclosure air during a second time interval t1 . It is shown that the time-averaged rate of enclosure air replacement is maximum when the rhythm is such that t0 t1 . (ii) Fresh air injected as a turbulent jet of duration t1, and withdrawal of mixed air during another interval, t2 . It is found that the spent power averaged during the cycle is minimum when t1 /t2 1. The concentration of fresh air in the enclosure increases in S-curve fashion, slow-fast-slow. The time scale of the fast (viral) portion of the S curve increases with the length scale of the enclosure and decreases with the Reynolds number based on port diameter and flow velocity. Numerical simulations of the flow confirm several features of the regimes documented theoretically.